Reformulation of Some Finite Raytracing Equations Through Quadric Surfaces of Revolution - Sadiq, Ibrahim A (Al-Nahrain Journal of Science, 2012)
This work exhibits analytical reformulation of four equations of finite raytracing throughquadric surfaces of revolution. This reformulation enhances comprehending the procedure of finiteraytracing firmly besides it shows how to obtain these formulas. The equations reformulated in thiswork clarified that the corresponding ones in [1] were merely typographically incomplete equations.